Efficient Vertical Transport of Black Carbon in the Planetary Boundary Layer. Issue 15 (7th August 2020) - Liu, Dantong; Hu, Kang; Zhao, Delong; Ding, Shuo; Wu, Yunfei; Zhou, Chang; Yu, Chenjie; Tian, Ping; Liu, Quan; Bi, Kai; Wu, Yangzhou; Hu, Bo; et al.
Abstract: Vertical distribution of black carbon (BC) determines the layer where its heating impacts exert. This study presents continuous and simultaneous measurements at surface and on a mountain site above the wintertime planetary boundary layer influenced by uplifted surface anthropogenic emissions. BC was observed efficiently transported upwards by daytime convective mixing. However, this vertical transport was less for other particulate masses. An about twofold higher BC mass fraction was thus present at mountain than surface, hereby a lowered single‐scattering albedo (SSA) by 0.06. This may be caused by the evaporative loss of condensed semivolatile materials, prevailing the secondary particulate formation, in a cleaner environment containing less precursors. The elevated BC mass corresponded with the most intensive solar radiation at midday, wielding more heating impacts over the planetary boundary layer (PBL). This phenomenon may apply to other remote regions where a reduced SSA will introduce more positive radiative effects. Plain Language Summary: Black carbon is strongly light absorbing, and its heating impacts in disturbing the stability of atmosphere depend on its location in the atmospheric column; thus, to understand its vertical distribution and transport mechanism is important. This study conducted simultaneous measurements at both sites on the surface and an elevated mountain site influenced by surface sources. We found that BC can be efficiently and vertically transported to the mountain site but not for the other more volatile substances. This is because a less secondary formation (due to lack of gas precursor) and some repartition process on the particle (back to the gas phase) may have led to a higher BC mass fraction in cleaner environment. This means in some remote places with less gas precursor present, BC may still reach and result in a high mass fraction, leading to more positive radiative effect. Key Points: Simultaneous measurements at both surface and top of boundary layer were performed for 1 month BC was transported efficiently to the top of PBL however not for other more volatile aerosols Higher BC mass fraction was observed over the top of boundary layer with lowered single‐scattering albedo by 0.06